2017
DOI: 10.1183/23120541.00148-2016
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial cryobiopsy in interstitial lung disease: experience in 106 cases – how to do it

Abstract: Transbronchial biopsy using forceps (TBB) is the first diagnostic technique performed on patients with interstitial lung disease (ILD). However, the small size of the samples and the presence of artefacts in the tissue obtained make the yield variable.Our objectives were 1) to attempt to reproduce transbronchial cryobiopsy under the same conditions with which we performed conventional TBB, that is, in the bronchoscopy unit without intubating the patient and without fluoroscopy or general anaesthesia; 2) to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 18 publications
(26 reference statements)
2
44
2
2
Order By: Relevance
“…• There is a need for standardization of TBCB procedures given the majority reported variability in diagnostic yield (50-100%) and complications (rate of pneumothorax from 0% up to about 30%) [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…• There is a need for standardization of TBCB procedures given the majority reported variability in diagnostic yield (50-100%) and complications (rate of pneumothorax from 0% up to about 30%) [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…The study showed that fewer pneumothoraces and moderate-to-severe bleeding were observed using fluoroscopy and bronchial blocker, respectively [23]. Alternatively, two scopes alternated during the procedure may avoid the need for intubation [24]. In a study by Bango-Álvarez et al [24], bleeding was controlled with this technique.…”
Section: Different Approachesmentioning
confidence: 99%
“…Alternatively, two scopes alternated during the procedure may avoid the need for intubation [24]. In a study by Bango-Álvarez et al [24], bleeding was controlled with this technique. Out of 106 patients, they obtained a diagnosis in 91 cases (86%), pneumothoraces were observed in 4.7% and no acute exacerbation of IPF or severe bleeding were observed.…”
Section: Different Approachesmentioning
confidence: 99%
“…Most centers perform TBLC under fluoroscopic guidance . A recent study, however, has described the procedure without the use of fluoroscopy and such a technique has been advocated in view of its simplicity . There is also a varying practice with the use of an occlusion balloon to block the biopsied segment .…”
Section: Introductionmentioning
confidence: 99%